The Triple Bottom Line Accounting from Scientia Sacra Perspective - Sari, Nur Astri; Shara, Yuni; Suhardianto, Novrys (Universitas Muhammadiyah Surakarta, 2023)
This article aimed to analyze the triple bottom line accounting concept from scientia sacra perspective. The alignment of the triple bottom line accounting from scientia Sacra perceptive is essential to dealing with crises in all aspects of life regarding corporate sustainability. Scientia sacra is the knowledge of reality that is at the heart of every revelation obtained through revelation and the intellectual intuition that cover the hearts and minds of human beings. This article employed the interpretative method. The triple bottom line concept from scientia sacra perspective is analyzed in ontological, epistemological, and axiological meanings. The ontological aspect of scientia sacra refers to the existence of God. In line with that, the ontological aspect in the triple bottom line also refers to the existence of God through religious ecocentrism or the spiritual dimension. In the epistemological aspect, the triple bottom line uses eco-theological principles from the Holly book. In the axiological aspect, the triple bottom line transforms from profit oriented to 3Ps (profit, people, planet) oriented. However, this transformative function has yet to be fully achieved since some companies still commit deviations, such as environmental pollution, due to their business activities.